The Enhancement of Spreadsheet Skills among Practitioners within Small Medium Accounting Firms - Maisurah Ku Bahador, Ku; Haider, Abrar; Mat Saat, Rafeah (International Journal of Engineering and Technology, 2018)
This study identifies electronic spreadsheet skills enhancement approaches among accounting practitioners in Malaysian small and medium accounting firms. Spreadsheet plays an important role for accounting practitioners and has also penetrated almost all accounting-related processes such as planning, budgeting, forecasting as well as decision-making responsibilities. This study uses a case study design with a qualitative approach as a strategy to identify skills development approaches. The findings conclude that formal education, experiential learning and job rotation and knowledge sharing among peers are the three main skills enhancement approaches which have emerged from utilising spreadsheet within the small and medium accounting firms. This study, thus makes significant contribution to the academic and professional bodies as well as to the industry, by providing theoretical base to develop skills related to spreadsheet as well as soft skills, indirectly, i.e. critical thinking and decision making skills for knowledge workers in general and accounting practitioners in particular.Â Â